Strengthen GH3536 manufactured by L-PBF with heat treatment and laser shock peening - Yi LIU; Xuewei FANG; Kexin TANG; Ke HUANG (Hanjie xuebao)
This paper examined GH3536 samples produced via laser powder bed fusion (L-PBF), analyzing their microstructure, mechanical properties, and residual stress under various heat treatment conditions. Surface residual stress was controlled by combining heat treatment and laser shock peening, with the impact of their sequence on residual stress also investigated. The results showed that large cooling stress during heat treatment caused some pore tearing, and heat treatment could not fully eliminate the surface residual tensile stress, which remained around +90 MPa. With an increasing number of impacts, residual stress improvement became more pronounced; after two impacts, the near-surface showed residual compressive stress at approximately −350 MPa. It was more effective in controlling residual tensile stress when laser shock peening was applied after heat treatment, enhancing overall performance. This study presented a new approach for the manufacturing and post-processing of GH3536, establishing a foundation for its engineering applications in aerospace.